ChemInform Abstract: A Mild and General One‐Pot Synthesis of Densely Functionalized Diaryliodonium Salts. Issue 6 (21st January 2016) - Qin, Linlin; Hu, Bao; Neumann, Kiel D.; Linstad, Ethan J.; McCauley, Katelyenn; Veness, Jordan; Kempinger, Jayson J.; DiMagno, Stephen G.
Abstract: A scalable synthesis is presented which gives access to a wide range of very densely functionalized diaryliodonium salts from aryl iodides under mild conditions.